The essential 55 : an award-winning educator's rules for discovering the successful student in every child - Clark, Ron, 1971- (New York : Hyperion, 2003)
Winner of the 2001 Disney teacher of the year award, Ron Clark presents fifty-five rules for everyday life that help students rise to their potential.
Responding to adults -- Making eye contact -- Congratulating a classmate -- Respect other students' comments, opinions, and ideas -- If you win, do not brag; if you lose, do not show anger -- If you are asked a question in conversation, ask a question in return -- Cover your mouth when you sneeze or cough and say excuse me -- Do not show disrespect with gestures -- Always say thank you when given something -- When you receive something, do not insult the gift or the giver -- Surprise others by performing random acts of kindness -- When grading other students' papers, give only the correct grade -- Follow along when we read together in class -- Answer all written questions with a complete sentence -- Do not ask for a reward -- You must complete your homework every day -- Subject transitions will be swift, quiet, and orderly -- Be as organized as possible -- When homework is assigned, do not moan or complain -- When a substitute teacher is present, all class rules still apply -- Follow the specific classroom protocols -- You may bring a bottle of water to class, you may not leave for a drink of water during class -- Know other teachers' names and greet them in the hall by name -- Keep yourself and the bathrooms clean and germ-free -- Greet visitors and make them feel welcome -- Do not save seats in the lunchroom -- Do not stare at a student who is being reprimanded -- Call me if you have a question about homework and leave a message--once -- The ABC's of etiquette -- After dining in the cafeteria or elsewhere, be responsible for your trash -- In a hotel room, leave a tip for the hotel workers who clean your room -- On a bus, always face forward -- When meeting new people, shake hands and repeat their names -- When offered food, take only your fair share -- If someone drops something and you are close to it, pick it up -- Hold the door for people rather than letting it close on them -- If someone bumps into you, say excuse me, even if it was not your fault -- On a field trip, enter a public building quietly -- On a field trip, compliment the place you are visiting -- During an assembly, do not speak or call out to friends -- At home, answer your phone in a polite and appropriate manner -- When returning from a trip, shake the hands of every chaperone -- On escalators, stand to the right, walk to the left -- When walking in line, keep your arms at your sides and move quietly -- Never cut in line -- No talking in a movie theater during the movie -- Do not bring Doritos into the school building -- If anyone is bullying you, let me know -- Stand up for what you believe in -- Be positive and enjoy life -- Live so that you will never have regrets -- Learn from your mistakes and move on -- No matter the circumstances, always be honest -- Carpe Diem -- Be the best person you can be -- A Few Tips for Dealing with Children -- Tips for Dealing with Parents -- Tips for Setting Punishments and Rewards.
Keywords: Teaching; Conduct of life; Enseignement; Morale pratique; 2; Lehrer; Unterricht; Guide (Descripteur de forme); Ratgeber